Imbalance of Th17 cells, Treg cells and associated cytokines in patients with systemic lupus erythematosus: a meta-analysis - Huang, Jinge; Li, Xiaolong; Zhu, Qingmiao; Wang, Meijiao; Xie, Zhijun; Zhao, Ting (Frontiers in Immunology, 2024)
Objective: This article aims to investigate the changes of T helper 17 (Th17) cells, regulatory T (Treg) cells and their associated cytokines in patients with systemic lupus erythematosus (SLE).Methods: Multiple databases were investigated to identify articles that explored Th17 cells, Treg cells and relevant cytokines in SLE patients. A random effects model was used for calculating pooled standardized mean differences. Stata version 15.0 was utilized to conduct the meta-analysis.The levels of Th17 cells, IL-17, IL-6, IL-21 and IL-10 were higher in SLE patients than in healthy controls (HCs), but the TGF-β levels were lower. The percentage of Treg cells was lower than HCs in SLE individuals older than 33. Among studies that had 93% or lower females, the percentage of Th17 cells was greater in patients than in HCs. However, the percentage of Treg cells was lower when the proportion of females was less than 90%. Patients with lupus nephritis or active SLE had an increased proportion of Th17 cells and a decreased proportion of Treg cells.The increased level of Th17 cells and related cytokines could be the main reason for the elevated Th17/Treg ratio in SLE. The percentages of Th17 and Treg cells were associated with gender, age, disease activity and kidney function. Furthermore, the reduced proportions of Treg cells may primarily result in a rise in the Th17/Treg ratio in older or active SLE patients.